Prospective Evaluation of Point-of-Care Ultrasound at a Remote, Multi-Day Music Festival. Issue 5 (1st October 2018) - Prager, Ross; Sedgwick, Colin; Lund, Adam; Kim, Daniel; Ho, Ben; Stachura, Maja; Gutman, Samuel
Abstract: Introduction: Point-of-Care Ultrasound (POCUS) has become an important diagnostic tool for hospital-based clinicians. This study assesses the role of POCUS at Pemberton Music Festival 2016 (Pemberton, British Columbia [BC], Canada), a remote mass gathering where physicians face limited resources, complex disposition decisions, and a dynamic clinical environment. Objectives: This study prospectively evaluated the impact of POCUS on patient diagnosis, management, and disposition based on the self-report of the study physicians. The authors hypothesized that having ultrasound available for use would aid in diagnostic and management decisions and would reduce the need to transfer patients off-site to other health care facilities, reducing impact on the acute health services in the host community. Methods: A handheld ultrasound was available for use by physicians in the main medical tent. All participating physicians self-reported their training and comfort using POCUS. After each POCUS scan, physicians completed a survey and recorded the indication for use, scans performed, and impact on patient diagnosis, management, and disposition. Results: In total, POCUS was used on 28 of the 686 patients treated in the main medical tent; POCUS was reported to narrow the differential diagnosis in 64% of cases and altered the working diagnosis in 21% of cases. Its use changed the management plan in 39% of patients. Its use was reported to reduce the burden on broader health care resource utilization in 46% of cases and prevented ambulance transport off-site in 32% of cases (nine cases in total). This corresponded to an absolute risk reduction of 1.3% for the percentage of patients transferred to hospital (PPTH; relative risk reduction of 53%). Conclusion: Physicians reported that POCUS improved the diagnosis, management, and disposition of select patients at a remote, multi-day music festival. Also, POCUS reduced ambulance transfers off-site and reduced the perceived burden on broader health care utilization. R Prager, C Sedgwick, A Lund, D Kim, B Ho, M Stachura, S Gutman .Prospective evaluation of point-of-care ultrasound at a remote, multi-day music festival .Prehosp Disaster Med .2018 ;33 (5 ):484 –489 .